2019
DOI: 10.1111/den.13382
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of magnifying colonoscopy for the diagnosis of ulcerative colitis‐associated neoplasia

Abstract: Background and Aim The aim of this investigation was to evaluate the efficacy of Japanese magnifying colonoscopic classifications for ulcerative colitis‐associated neoplasia (UCAN). Methods We reviewed the colonoscopy records from 2011 to 2018 at our institutions and identified cases of endoscopically or surgically resected UCAN observed by magnifying narrow‐band imaging (NBI) endoscopy and magnifying chromoendoscopy. Association between magnifying endoscopic classification and histopathological findings was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 28 publications
1
29
0
3
Order By: Relevance
“…In our sub‐analysis, we showed that the strength of EC‐NBI was its time savings compared with EC staining and even biopsy. Our results are consistent with the concepts of conventional magnifying or non‐magnifying image‐enhanced endoscopy 30–32 . Recently, multiple biopsies from all segments of the colorectum have been recommended to evaluate a patient's inflammation severity and extent 33 .…”
Section: Discussionsupporting
confidence: 88%
“…In our sub‐analysis, we showed that the strength of EC‐NBI was its time savings compared with EC staining and even biopsy. Our results are consistent with the concepts of conventional magnifying or non‐magnifying image‐enhanced endoscopy 30–32 . Recently, multiple biopsies from all segments of the colorectum have been recommended to evaluate a patient's inflammation severity and extent 33 .…”
Section: Discussionsupporting
confidence: 88%
“…The procedures carried out in our center used high‐definition endoscopes (Olympus 260/290 series), without the use of magnifying endoscopy. Magnifying endoscopy is a promising modality in the optical diagnosis of IBD lesions; however, we are unable to comment on the role of this technology in IBD surveillance. However, given that magnifying endoscopy is not in widespread in the West, our results are likely to reflect “real‐life” practice.…”
Section: Discussionmentioning
confidence: 88%
“…Of the 31 studies[ 5 , 13 - 42 ], 11 were retrospective [ 5 , 13 - 22 ], and 20 were prospective[ 23 - 42 ]. Seven studies[ 14 - 20 ] used the JNET classification alone, 21 studies[ 22 - 42 ] used the Pit pattern classification alone, and only 3 studies[ 5 , 13 , 21 ] used both the JNET and Pit pattern classifications in the same population. Thirteen studies[ 5 , 13 - 16 , 18 - 21 , 24 , 28 , 35 , 41 ] used narrow-band imaging magnifying endoscopy (NBI-ME), 13 studies used magnifying chromoendoscopy[ 22 , 25 - 27 , 29 , 30 , 32 - 35 , 37 , 38 , 42 ], and the other studies used BLI-magnification[ 17 , 23 ] ( n = 2), NBI[ 31 , 39 ] ( n = 2), and chromoendoscopy[ 36 , 40 ] ( n = 2).…”
Section: Resultsmentioning
confidence: 99%